2015
DOI: 10.18632/oncotarget.3154
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical and genomic profiles of diffuse large B-cell lymphomas: Implications for targeted EZH2 inhibitor therapy?

Abstract: Enhancer of Zeste Homolog 2 (EZH2) plays an essential epigenetic role in Diffuse Large B Cell Lymphoma (DLBCL) development. Recurrent somatic heterozygous gain-of-function mutations of EZH2 have been identified in DLBCL, most notably affecting tyrosine 641 (Y641), inducing hyper-trimethylation of H3K27 (H3K27me3). Novel EZH2 inhibitors are being tested in phase 1 and 2 clinical trials but no study has examined which patients would most benefit from this treatment. We evaluated the immunohistochemical (IHC) met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 38 publications
3
24
1
2
Order By: Relevance
“…S5B). Interestingly, one PMBL patient presented an EZH2 Y641 mutation, adding to the debate of which DLBCL subtypes might benefit from EZH2 inhibitor treatment (26). CREBBP mutations were identified in 31.3% of GCB patients and 6.2% of ABC patients, corroborating previous studies (17), but were also found in 24.2% of "other" and 11.1% of PMBL ( Fig.…”
Section: Lymphopanel Ngs Identifies Mutations With Potential Treatmensupporting
confidence: 85%
See 1 more Smart Citation
“…S5B). Interestingly, one PMBL patient presented an EZH2 Y641 mutation, adding to the debate of which DLBCL subtypes might benefit from EZH2 inhibitor treatment (26). CREBBP mutations were identified in 31.3% of GCB patients and 6.2% of ABC patients, corroborating previous studies (17), but were also found in 24.2% of "other" and 11.1% of PMBL ( Fig.…”
Section: Lymphopanel Ngs Identifies Mutations With Potential Treatmensupporting
confidence: 85%
“…Ion Torrent Personal Genome Machine (PGM) Sequencing and PGM data analysis was performed as described previously (26) and detailed in Supplementary Methods. Variant analysis was performed using an in-house generated bioinformatics pipeline, detailed in Supplementary Methods and Supplementary Fig.…”
Section: Ngs Experiments and Data Analysismentioning
confidence: 99%
“…Thirty four genes relevant to lymphomagenesis (listed in Supporting Information Table V) were analyzed using the multiplexed PCR‐based targeted library Ion AmpliSeq™ technology, as previously described . Sequencing performances and whole nucleotide variations are respectively given in Supporting Information Table VI and Supporting Information Data as a combined .vcf file.…”
Section: Methodsmentioning
confidence: 99%
“…Libraries were prepared from 10 ng of genomic DNA with primers from our previously reported Lymphopanel 21,26 targeting the XPO1 E571K nucleotide variant (Online Supplementary Methods).…”
Section: Ion Torrent Personal Genome Machine™ (Pgm) Sequencingmentioning
confidence: 99%